Standar Nafkah Perkawinan Poligami Perspektif Hukum Islam dan Undang-Undang Perkawinan No. 1 Tahun 1974 : Studi Putusan Poligami di Pengadilan Agama Islam Jombang Tahun 2021 - 2023 - Masnun, Muhammad; Sukardi, Imam (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
This research aims to examine the standard of marital maintenance (nafkah) in polygamous marriages from the perspective of Islamic law and Marriage Law No. 1 of 1974. The method used is normative legal research with a case study of polygamy rulings at the Jombang Religious Court from 2021 to 2023. The results show that the practices at the Jombang Religious Court have fulfilled the principle of minimum sufficiency according to Islamic law and statutory regulations, although discrepancies exist in interpreting the form and amount of maintenance. These findings are expected to contribute to strengthening regulations and judicial practices to protect wives' rights in polygamous marriages. Keywords: Polygamy, Fiqh, Legislation